Investigation of the effect of a probiotic-supplemented diet on the haemocyte proteome of the abalone Haliotis midae - Dias, Valera Lucena (Department of Molecular and Cell Biology, 2017)
Haliotis midae is an economically important South African abalone species which has been cultured since the 1990s. H. midae farming constitutes approximately 93% of the country's total marine aquaculture industry. However, the slow growth rate of this animal and the potential for disease outbreaks remain a concern for farmers. Therefore, government and private institutions have joined efforts to investigate ways of enhancing abalone production, to increase abalone growth rates and improve disease resistance. Several studies have shown that probiotic microorganisms can significantly increase the growth rate and disease resistance of H. midae. To date, no comprehensive studies have been conducted to characterise these physiological improvements at the molecular level. Thus, the aim of this study was to evaluate the effect of a probiotic-supplemented diet on the haemocyte proteome in H. midae. Two probiotic-strains, Vibrio midae SY9 and Debaryomuces hansenii AY1, were introduced into H. midae via a kelp-based feed. Changes in the haemocyte proteome were analysed using isobaric tag for relative and absolute quantification (iTRAQ) coupled with LC-MS/MS. A total of 128 haemocyte proteins were identified. Proteins that were found to vary significantly in their expression levels in haemocytes sampled from abalone fed the probiotic-supplemented diet were identified as COP9 signalosome subunit 4, phosphorylase, T-complex protein 1 subunit gamma, V-type proton ATPase subunit B, Rab 1 and Ra-related protein Rab 1A. Differential expression of COP9 signalosome subunit 4 (up-regulated) and Ras-related protein Rab 1A (down-regulated) was confirmed by western blot analysis. Bioinformatics analysis revealed proteins with immune class GO terms that functioned in metabolism, apoptosis, cell adhesion, immune response, stress response, and response to endogenous and external stimulus. Hierarchical clustering analyses showed that proteins with similar expression patterns mostly belonged to the same immune classes. Analysis of protein interaction networks indicated that all the differentially expressed proteins may indirectly interact with each other. It was also found that the neurotrophic tyrosine kinase receptor was the central molecule within the interaction network, suggesting that this protein may play a crucial role within the protein interaction network that contains all the differentially expressed proteins. Biochemical pathway analysis indicated that phagosomal maturation was the most significant canonical pathway identified, in which V-type proton ATPase and Ras-related protein Rab have fundamental importance. Changes in Ras-related protein Rab 1A expression were further investigated in the cytosolic and membrane fractions of haemocyte cells using western blot analysis and cellular immunochemistry. The expression of this protein was found to be down-regulated both in cytosolic and membrane fractions from haemocytes sampled from H. midae fed a probioticsupplemented diet. Although an association between Ras-related protein Rab 1A and F-actin (cell cytoskeleton) was not detected, confocal microscopy confirmed Ras-related protein Rab 1A down-regulation. Thus, results from this study suggest that Ras-related protein Rab 1A may play a key role in H. midae immune response, when this species of abalone is fed with a probiotic-supplemented diet. This is the first time that a large-scale proteomics approach has been used to investigate proteome changes in haemocytes sampled from H. midae fed a probiotic-supplemented diet. The findings of this study, regarding the protein profile, interaction networks, molecular pathways and a putative molecular indicator of H. midae immune response, provide a foundation from which future studies can be conducted in order to increase our understanding of how probiotics affect the abalone immune system.